Environmental drivers of wild bee reproductive performance across a South American dryland ecoregion - Aranda-Rickert, Adriana; Peralta, Guadalupe; Diniz, Mary E. R.; Tálamo, Andrés; Allasino, Mariana Laura; Andrada, Franco; Arcárgel, Andrea E.; Cagnolo, Luciano; Campanella, María Victoria; Chacoff, Natacha P.; Chirilá, María Virginia; Díaz Casas, Antonella Y.; et al. (The Royal Society, 2025)
The reproductive performance of wild bees is a key determinant of their population persistence. However, few studies have directly examined the environmental drivers of demographic processes using a geographically broad approach. In this study, we explored how biotic and abiotic factors influence the reproduction of solitary, cavity-nesting bees across the Monte Desert ecoregion in Argentina. Using artificial nests and a standardized sampling spanning 2000 km and 20° of latitude, we related key reproductive metrics—nest establishment, offspring production and offspring survival—to latitude, climate and biotic factors (flower abundance, vegetation cover and brood parasitism). Climate was the strongest predictor of bee reproductive performance: warm, humid conditions during the nesting period were associated with reduced nest establishment and offspring survival. Brood parasitism further reduced offspring survival. Across the Monte Desert’s latitudinal gradient, nest establishment peaked at mid-latitudes, while offspring production and survival increased towards higher latitudes. These general patterns matched those of M. leucografa, the most abundant bee species. These findings highlight the sensitivity of wild bee reproduction to climatic conditions, particularly during the nesting period. Our study advances our understanding of the potential impacts of climate change on Neotropical wild bees, where extensive areas are experiencing dramatic land-use changes.